The Reading Culture of Professionals and Managers in Slovenian Libraries - Švab, Katarina; Vilar, Polona; Jug, Tjaša (Bralni vzori 2, 2025)
The reading culture of professional and managerial staff in Slovenian libraries has never been comprehensively analysed. This gap has been addressed through several studies conducted as part of the targeted research programme "Reading Role Models: Reading Habits of Professionals in Kindergartens, Schools, Faculties, and Public Libraries" (CRP V5-2361). This paper focuses on the results of two online surveys conducted in 2024 among Slovenian library staff. A total of 797 professionals and 76 managers working in Slovenian libraries participated in the surveys. The article presents the main findings, with particular attention to the various activities, projects, and institutions with which Slovenian libraries collaborate. Library staff consider reading as a core value and dedicate a significant portion of their free time to it, as not all libraries allocate time for reading within their weekly work schedules. This explains their strong commitment to promoting reading culture among their users in various ways.